Investigation of the beliefs and assessment of the security feeling in primary education in Greece in relationship to rapid onset natural disasters. - Akylina Mereli; Niki Evelpidou; Assimina Antonarakou; Hara Drinia; Maria Mereli; Maria Tzouxanioti (International Journal of Educational Research Review, 2022)
The aim of the research is the awakening, participation and alertness of educators and students of Primary Education schools in Greece when it comes to rapid onset Natural Disasters pre-emption. The aim is the alertness of educators, as well as students of school units, so that they are able to face rapid onset natural disasters with prudence and composure, both during them, by putting themselves in the minimum possible danger, and after their finish, by taking part in the rehabilitation of “damages” of any kind. At an early stage, through the distribution of two questionnaires, one for educators and one for students, we invited the participants to answer questions relevant to their status and knowledge, when it comes to rapid onset natural disasters and their safe living in their school environment. In total, the participants exceeded two thousand (2,000) persons. One thousand twenty seven (1,027) educators, serving the Primary Education, and nine hundred eighty four (984) random students from all over the country, answered the digital questionnaires created through the application ArcGIS Survey123 (part of Geospatial Cloud by Esri), which is an integrated solution to the creation, distribution and analysis of survey data. From the statistical analysis of their answers, their beliefs regarding the subject examined arose and the proposed means of action is profiled, so that persons participating on the educational procedure can achieve their meaningful training, in order for them to feel safer and more aware, imparting their knowledge regarding rapid onset natural disasters. Their considering training programs about natural disasters necessary is clear, as the majority of them accept that any natural disaster is liable to occur while they are at school. The conducted research showed that the knowledge of educators and students regarding their responsibilities, as well as the necessary items and services which are essential during the occurrence of the natural phenomenon, as well as after its finish, seem to be inadequate.